Early stationary phase culture supernatant accelerates growth of sputum cultures collected after initiation of anti‐tuberculosis treatment. (29th November 2013) - Kolwijck, E.; Friedrich, S. O.; Karinja, M. N.; van Ingen, J.; Warren, R. M.; Diacon, A. H.; Drancourt, M.
Abstract We investigated the effect of Mycobacterium tuberculosis culture supernatant added to sputum cultures collected during the first 8 weeks of anti‐tuberculosis treatment. With ongoing treatment duration, time to culture positivity decreased significantly in supernatant‐enriched cultures, possibly due to stimulation of dormant or slowly metabolizing M. tuberculosis cells.